Returns to Higher Education in Chile and Colombia - Carolina González-Velosa; Graciana Rucci; Miguel Sarzosa; Sergio Urzúa (Inter-American Development Bank (IDB), 2015)
In the last decades, countries in Latin America and the Caribbean have experienced a dramatic increase in the levels of higher education enrollment. Using administrative data from Chile and Colombia, we find that this phenomenon is not always associated with higher private individual returns. In both countries, there is a significant dispersion in the net returns to higher education and a significant proportion of graduates could be facing negative returns. This means that, for many higher education graduates, net earnings might have been higher if they had not earned a higher education degree. We hypothesize that while there have been major policy efforts to increase coverage, institutional arrangements that encourage quality and relevance has been insufficient. Corrective measures in this direction are urgent. Sustainable growth requires a labor force with relevant skills and capabilities. In light of our results, it is not clear that the higher education systems in these countries are delivering these outcomes.
hdl:11319/6858
Keywords: 330; Higher education; returns to higher education; heterogeneity; inequality; skills; productivity